Approach with initiative or hold on passively? The impact of customer-perceived dependence on customer forgiveness in service failure - Chen, Xin; Guo, Shuojia; Xiong, Jie; Hao, Shuyi (Frontiers in Psychology, 2022)
Service failure is almost inevitable with the intensifying competition in the service market and expectation of heterogeneous customers. The customer–firm relationship can significantly influence customers’ subsequent attitudes and behaviors to the service provider when they encounter service failure. This study proposes a theoretical model to examine how customer-perceived dependence affects their forgiveness toward a service failure in attribution logic. According to an experiment with 138 and a survey with 428 commercial bank customers, we used a multivariate approach to validate our model. The results show that relationship-valued dependence (RVD) leads to external attribution, which is positively related to customer forgiveness. In contrast, switching-cost dependence (SCD) leads to internal attribution, which is negatively related to customer forgiveness. The relationship length is a relevant contextual factor that acts as a negative moderating factor. Our study contributes to the service recovery literature by elucidating the underlying process of forgiveness with the presence of the customer–firm dependence relationship.